Invasion of the choroid plexus epithelium by Neisseria meningitidis is differently mediated by Arp2/3 signaling and possibly by dynamin dependent on the presence of the capsule. Issue 7 (19th August 2021) - Herold, Rosanna; Sünwoldt, Gina; Stump-Guthier, Carolin; Weiss, Christel; Ishikawa, Hiroshi; Schroten, Horst; Adam, Rüdiger; Schwerk, Christian
ABSTRACT: Neisseria meningitis ( Nm ) is a human-specific bacterial pathogen that can cause sepsis and meningitis. To cause meningitis Nm must enter the central nervous system (CNS) across one of the barriers between the blood and the brain. We have previously shown that a capsule-depleted Serogroup B strain of Nm displays enhanced invasion into human choroid plexus (CP) epithelial papilloma (HIBCPP) cells, which represent an in vitro model of the blood–cerebrospinal fluid barrier (BCSFB). Still, the processes involved during CNS invasion by Nm, especially the role of host cell actin cytoskeleton remodeling, are not investigated in detail. Here, we demonstrate that invasion into CP epithelial cells by encapsulated and capsule-depleted Nm is mediated by distinct host cell pathways. Whereas a Serogroup B wild-type strain enters HIBCPP cells by a possibly dynamin-independent, but actin related protein 2/3 (Arp2/3)-dependent mechanism, invasion by a capsule-depleted mutant is reduced by the dynamin inhibitor dynasore and Arp2/3-independent. Both wild-type and mutant bacteria require Src kinase activity for entry into HIBCPP cells. Our data show that Nm can employ different mechanisms for invasion into the CP epithelium dependent on the presence of a capsule. Abstract : Involvement of Arp2/3 and possibly dynamin during invasion of choroid plexus epithelial cells by Neisseria meningitidis is dependent on the presence of the bacterial capsule.